Media Literacy, Hoax And Young Voter Behavior Towards The 2024 President Election Of Indonesia - Rahma Santhi Zinaida; Zaid Amin; Genoveva Regina V,H Regina V,H; Ria Aprinda (Jurnal Ilmu Sosial Mamangan, 2024)
The attitude of youth provides awareness to contribute to the progress of this country and one of them is political participation. The development of information technology has produced a variety of fake news/hoaxes which are troubling all groups, especially the influence of the millennial generation as first-time voters in the 2024 presidential election process. One of the causes of widespread fraud is the freedom of the millennial generation in spreading hoax news on social media and the lack of understanding of critical media literacy. . For this reason, it is important to carry out this research in the city of Palembang by identifying the problem, namely that the spread of hoax news is feared to influence political awareness in the political participation of novice voters who are dominated by students. Based on the problem above, the problem formulation and objective is to analyze the influence of social media literacy on the political awareness of novice voters in the city of Palembang in the spread of hoax news ahead of the 2024 presidential election? The state of the art in this research is that the majority of previous research has focused on the influence of social media on voting decisions, but there has been no research that specifically looks at the influence of media literacy programs initiated by the government to increase the political awareness of first-time voters. Because before the decision to vote, there is a process of awareness of the importance of a person's involvement in voting so that the voting decision will be in accordance with his or her beliefs. The theories used are new media literacy theory (Tzu-Bin Lin) and three patterns of political awareness (Almond & Verba). This research uses a quantitative non-experimental ex post facto approach. The subjects of this research were novice voters in Palembang City at student level, with an age range of 19-24 years. The sample was taken from 77 students in Palembang City. Primary data was taken using a questionnaire and secondary data from literature reviews and related documents. Researchers used clustering sampling techniques, Likert measurement scales and linear regression analysis techniques.